Republic of Kazakhstan : Financial Sector Assessment Program Update-Technical Note-Bank Profitability and Competition. (IMF Staff Country Reports; Country Report ;, 2004)
This technical note explores the reasons for a comparatively high interest rate spread in Kazakhstan in the context of competition in the banking sector. In spite of significant gains in efficiency made in recent years, operational costs and provisioning for loan losses remain high compared with some other economies. Rapid progress is being made in developing an efficient banking sector, and further improvements will depend on good supervisory and regulatory enforcement. The level of financial intermediation, although high among neighboring countries and growing, is still low in broader comparisons.